Perfil morfológico de voleibolistas de altos logros. Revisión - Fernandez, J. A.; Rubiano, P. A.; Hoyos, L. A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2017)
The purpose of this article is identify the morphological profile of the volleyball players of elite women. METHOD: Search was made and the various specialized databases was developed to identify studies published on this topic since 2000. We analyzed the variables of body composition (CC), materials, methods and techniques used in each of the studies RESULTS: A total of 65 papers and 76 different variables were identified. Conclusions: the variables most used in the measurement of body composition and the morphological profile of the elite women volleyball players were identified.